The Effect of Differentiated Learning on Students' Learning Outcomes of Pancasila Education - Susi Susi; Siti Mariyatul Koimah; Roni Rustandi; Nurdiyana Nurdiyana (Yayasan Keluarga Guru Mandiri, 2025)
This research investigates the influence of differentiated learning models on student achievement in Pancasila Education at MTS Asmaul Husna, Tangerang Regency. Differentiated learning is a learning approach that adjusts content, process, and product to meet differences in student readiness, interest, and learning style. The study used a quantitative design with a quasi-experimental method, specifically the pretest–post-test nonequivalent control group design. The participants were class VII A (26 students) as the experimental group and class VII B (22 students) as the control group, determined through saturated sampling. Data were gathered using multiple-choice tests and analyzed for normality, homogeneity, and independent-samples t-tests. The findings revealed that the experimental group's mean post-test score was 82.58, compared with 74.18 in the control group. The significance value (Sig. 2-tailed) of 0.006 0.05 indicates a significant difference. These results demonstrate that differentiated learning has a positive effect on learning outcomes. This study enriches educational knowledge by presenting empirical evidence of the effectiveness of differentiated learning in improving student performance and can serve as a reference for future pedagogical innovation. This research contributes theoretically by enriching knowledge and practically by guiding effective differentiated learning.